Food, Media and Contemporary Culture: The Edible Image by Peri Bradley (Ed.): book review; Journalism & Mass Communication Quarterly; Vol. 94, iss. 4 - Fell E. V. Elena Vladimirovna (2017, 2017)
Title screen